In the zone of complexity: science and the sacred - Rolston, Holmes, 1932-2025, author; Tamarack Press, publisher (Colorado State University. Libraries, 2005)
A contemporary surprise has been waking up to deep space and deep time, to a hospitable universe, to nature's simplicity and complexity, to information in earth history, to struggle for survival and adapted fit, to human uniqueness, to an Earth ethics, to spirit in nature, to the numinous, to a cruciform nature.
Photographs by Linda Connor.
Keywords: universe; simplicity; environmental ethics; humans; crisis; ecology; nature; culture; complexity; evolution